A contribution to the surgical treatment of venous disorders of the lower limbs. - Molina V., Lucas (2015)
It is provided in this paper an alternative technique that complements the routine methods of classical saphenectomy in the dependent territories of superficial varicose veins. We call this change "FLEVOEXTRACCION SIDE WITH SIMULTANEOUS LIGATION". The goal achieved by this technique has been reducing immediate bleeding to venous avulsion of the hematoma and bruising after surgery tegumentaria. We believe that previous ties prevent possible complications of the conventional processes: organization of hematoma, venous thrombosis, embolism and infection. This procedure allows preserving the aesthetics of the limbs treated to reduce the number of surgical incisions. Presented for consideration a series of 24 case histories, equivalent to 29 lower limbs of patients with varicose veins, operated by the Department of General Surgical Hospital of Toquepala, dependence on Southern Peru Copper Corporation.